Evaluasi Program Pemeriksaan Gigi pada Ibu Hamil Sebagai Upaya Deteksi Dini Komplikasi Kehamilan di Puskesmas Kaliwates dan Puskesmas Banjarsengon Selama Tahun 2019 - Nadia Dian Rosanti; Dinar Rizqi Perwitasari (Poltekkes Kemenkes Kendari, 2021)
Minister of Health Regulation Number 89 of 2015 regulates the implementation of dental and oral health services for pregnant women. Unhealthy teeth and mouth conditions during pregnancy can increase the risk of pregnancy complications. Researchers evaluated the implementation of the Dental Examination Program for pregnant women during 2019 in Jember Regency. Data were obtained through in-depth interviews with five informants, document review and direct observation at Kaliwates Health Center and Banjarsengon Health Center. The results of the evaluation of the implementation of the Dental Examination Program for pregnant women have generally been carried out. There was an increase in preeclampsia cases at the Kaliwater Health Center in 2019 compared to 2018, and a decrease in preeclampsia cases at the Banjarsengon Health Center compared to 2018. It is necessary to improve the management of the Dental Examination Program services for pregnant women to achieve optimal health goals for pregnant women.